Glass composition

By developing a glass composition that can degrade under physiological conditions, the problem of poor environmental pollution and mitigation effect of non-degradable particulate materials in existing dentin desensitization compositions is solved, and long-term dentin desensitization effect and environmentally friendly degradation characteristics are achieved.

CN119683851APending Publication Date: 2025-03-25IR SCI INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411889886.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-05-14
Filing Date
2019-09-04
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The non-degradable particulate materials used in existing dentin desensitization compositions have problems with environmental pollution and long-term unreliable mitigation effects.

Method used

A glass composition is developed that contains about 50 mol% to 95 mol% of B2O3 and about 5 mol% to 50 mol% of other glass components, capable of losing at least 5 mass% in the buffered saline solution within 24 hours and comprises particles of about 1 μm to 50 μm in size to block dentin tubules.

Benefits of technology

The glass composition degraded under physiological conditions, providing long-term dentin desensitization effects, reducing the risk of environmental pollution, and forming protective precipitates through fluoride release, further reducing dentin sensitivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683851A_ABST
    Figure CN119683851A_ABST
Patent Text Reader

Abstract

The present invention provides a glass composition comprising from about 50 mol% to about 95 mol% of B2O3; from about 5 mol% to about 50 mol% of one or more glass components selected from the group consisting of Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO, and ZnO. The glass composition includes less than 30 mol% of Rb2O. The glass composition is a quaternary system. The glass composition is a particulate material including particles having a size of about 1 to about 50 [mu] m. When exposed to a buffer salt solution, the glass composition loses at least 5 mass% within 24 hours. The glass composition can be used for dentin desensitization. The invention also provides a dentin desensitization composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with the application date of September 4, 2019, application number 201980058257.3, and invention name “Glass Composition”. Technical Field

[0002] The present invention relates to glass compositions for use in dentin desensitizing compositions. Background Art

[0003] The following paragraphs are not an admission that anything discussed in them is prior art or part of the knowledge of a person skilled in the art.

[0004] Dentin sensitivity is tooth pain caused by the response of exposed dentin surfaces to stimuli (e.g., heat, vapor, touch, osmotic, chemical, or electrical stimulation). Dentin sensitivity may be caused by gingival recession (gingival recession) of exposed root surfaces, loss of cementum and smear layers, tooth wear, acid erosion, periodontal root planing, or tooth bleaching.

[0005] Dentin contains thousands of microscopic tubular structures radiating outward from the pulp. Changes in the flow of the plasma-like biological fluid present in the dentinal tubules trigger mechanoreceptors on the nerves located in the pulp site, causing a pain response. This hydrodynamic flow can be increased by cold, air pressure, dryness, sugar, acid (dehydrating chemicals), or force acting on the tooth. Hot or cold foods or drinks and physical stress are typical triggers for those who experience tooth sensitivity.

[0006] There is currently no recognized gold standard treatment that reliably provides long-term relief from the pain of tooth hypersensitivity. However, treatments can be divided into office-based treatments (i.e., intended to be performed by a dentist or dental therapist); or treatments that can be performed at home, either over-the-counter or by prescription.

[0007] The putative mechanism of action of these treatments is occlusion of the dentinal tubules, or desensitization of nerve fibers / blockage of nerve conduction. Summary of the invention

[0008] The following introduction is intended to introduce the specification to the reader, but not to define any invention. One or more inventions may exist in a combination or sub-combination of the device elements or method steps described below or in other parts of this document. The inventors do not waive or deny their rights to any other inventions disclosed in this specification but not described in the claims.

[0009] An example of a dentin desensitizing composition known in the art is disclosed in PCT Publication No. WO2007144662A1. The disclosed toothpaste includes a bioactive glass containing strontium. The disclosed bioactive glass occludes the dentin tubules and causes precipitation and crystallization of carbonated hydroxyapatite. The disclosed bioactive glass is designed to degrade at the same rate as the rate of induced tissue ingrowth.

[0010] One example of a dentin desensitizing composition known in the art is disclosed in U.S. Pat. No. 5,735,942. The disclosed toothpaste includes a mineral component consisting of CaO, Na2O, P2O5, and SiO2. The disclosed mineral composition chemically reacts with the surface of dentin and binds tightly to the tooth structure.

[0011] One or more of the described embodiments seek to address or ameliorate one or more disadvantages associated with dentin desensitizing compositions, including non-degradable particulate materials that block dentin tubules. In some embodiments, the disclosed particulate materials substantially degrade under ambient conditions and over a period of time exceeding 12 to 24 hours. In some embodiments, the disclosed particulate materials provide controlled release of fluoride over the same period of time.

[0012] In some embodiments, the present invention provides a glass composition comprising about 50 mol% to about 95 mol% B2O3; about 5 mol% to about 50 mol% of a glass component selected from the group consisting of: Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO, ZnO, and any combination thereof; 0 mol% CuO; less than 0.1 mol% BaO; less than 0.1 mol% P2O5, wherein the glass composition comprises less than 30 mol% Rb2O. When exposed to a buffered salt solution, the glass composition loses at least 5% mass within 24 hours, and the glass composition is a particulate material comprising particles having a size of about 1 μm to about 50 μm. The glass component is not only composed of B2O3 and Na2O.

[0013] In some examples of glass compositions according to the present disclosure, less than 20 mol %, eg, less than 15 mol %, less than 10 mol %, or less than 5 mol %, of the glass composition is CaO, MgO, and Na2O.

[0014] The glass composition may further comprise up to about 30 mol % of a fluoride, wherein the fluoride is in the form of CaF2, NaF, Na2PO3F, KF, or SnF2.

[0015] In other embodiments, the present invention provides a glass composition for desensitizing dentin, the glass composition comprising about 50 mol% to about 95 mol% B2O3; about 5 mol% to about 50 mol% of a glass component selected from the group consisting of: Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO, ZnO, and any combination thereof, wherein the glass composition comprises less than 30 mol% Rb2O. When exposed to a buffered saline solution, the glass composition loses at least 5% by mass within 24 hours, and the glass composition is a particulate material comprising particles having a size of about 1 μm to about 50 μm.

[0016] In some examples of glass compositions, less than 20 mol %, eg, less than 15 mol %, less than 10 mol %, or less than 5 mol % of the glass composition is CaO, MgO, and Na2O.

[0017] The glass composition may further comprise up to about 30 mol % of a fluoride, wherein the fluoride is in the form of CaF2, NaF, Na2PO3F, KF, or SnF2.

[0018] In other embodiments, the present invention provides a glass composition comprising: a fluoride providing about 5 mol % to about 10 mol % of CaF2, SnF2, NaF, KF, or any combination thereof; and about 90 mol % to about 95 mol % of a combination of B2O3, Na2O, MgO, and CaO, wherein boron, magnesium, a combination of Na and any K, and a combination of Ca and any Sn in the glass composition are present in an element ratio of about 20: about 4: about 6: about 3, respectively.

[0019] One example of such a specific glass composition according to the present invention includes about 50 mol % B2O3, about 15 mol % Na2O, about 20 mol % MgO, about 10 mol % CaO, and about 5 mol % CaF2.

[0020] The glass composition according to the invention may be formulated as a dentin desensitizing composition, for example, a toothpaste, a prophylactic paste, a tooth varnish, a mouthwash, a tooth gel or an adhesive.The dentin desensitizing composition according to the invention is substantially anhydrous.

[0021] The glass composition according to the invention can be used for desensitizing dentin, for example, in a method comprising applying to the dentin of an individual a toothpaste, a prophylactic paste, a tooth varnish, a mouthwash, a tooth gel or an adhesive according to the invention.

[0022] The glass composition according to the present invention can be prepared from the corresponding bulk glass. The chemical formula between the bulk glass and the particulate material is the same. Another aspect of the present invention is a bulk glass having a chemical formula as disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings.

[0024] Figure 1 is a comparison of the mean values ​​of the surface profile of the resin composite after 20,000 brushing cycles with Gel 7 HT toothpaste ("Gel") and with Gel 7 HT toothpaste formulated with the glass composition according to the present invention ("Gel+Additive").

[0025] Figure 2 The toothpaste was Gel 7 HT ("Gel") and the toothpaste was Colgate formulated with the glass composition according to the present invention. TM Mean comparison of the surface profile of the resin composites after 20,000 brushing cycles for Enamel Health Sensitivity Relief Toothpaste ("Colgate EN+ Additvie").

[0026] Figure 3 Gel 7 HT toothpaste ("Gel") and Colgate TM Mean comparison of the surface profile of the resin composite after 20,000 brushing cycles with an optical whitening toothpaste ("Colgate Optic").

[0027] Figure 4 Gel 7 HT toothpaste ("Gel") and Colgate TM Mean comparison of the surface profile of the resin composite after 20,000 brushing cycles for the enamel health relief toothpaste ("Colgate EN").

[0028] Figure 5 Gel 7 HT toothpaste ("Gel") and Sensodyne TM Mean comparison of the surface profiles of the resin composites after 20,000 brushing cycles with whitening, restoring and protective toothpaste ("Sensodyne").

[0029] Figure 6 Gel 7 HT toothpaste ("Gel+Additve") formulated with the glass composition and Sensodyne TMMean comparison of the surface profiles of the enamel surface after 20,000 brushing cycles for whitening, restoring and protective toothpaste ("Sensodyne").

[0030] Figure 7 The glass composition was used to prepare Gel 7 HT toothpaste ("Gel+Additvie") and Colgate TM Mean comparison of the surface profile of the enamel surface after 20,000 brushing cycles of Enamel Health Sensitivity Relief Toothpaste ("Colgate EN+Additive").

[0031] Figure 8 is a comparison of the mean surface profiles of tooth enamel surfaces after 20,000 brushing cycles using Gel 7 HT toothpaste ("Gel") and Gel 7 HT toothpaste formulated with the glass composition ("Gel+Additive").

[0032] Fig. 9 The toothpaste was prepared with Gel 7 HT ("Gel+Additive") prepared with the glass ingredients and with Colgate TM Mean comparison of the surface profile of tooth enamel surfaces after 20,000 brushing cycles for optical whitening toothpaste ("Colgate Optic").

[0033] Fig.10 The toothpaste was prepared with the glass composition Gel 7 HT ("Gel+Additive") and with Colgate TM Mean comparison of the surface profile of tooth enamel surfaces after 20,000 brushing cycles with Enamel Health Sensitivity Relief Toothpaste ("Colgate EN").

[0034] Fig.11 is a scanning electron micrograph of an exemplary glass composition according to the present invention after being immersed in simulated body fluid (SBF) at 37° C. for 30 minutes.

[0035] Fig.12 is a scanning electron micrograph of an exemplary glass composition according to the present invention after being exposed to simulated body fluid (SBF) at 37° C. for 3 hours.

[0036] Fig.13 is a scanning electron micrograph of an exemplary glass composition according to the present invention after being exposed to simulated body fluid (SBF) at 37° C. for 12 hours.

[0037] Fig.14 is another scanning electron micrograph of an exemplary glass composition according to the present invention after being exposed to simulated body fluid (SBF) at 37° C. for 12 hours. DETAILED DESCRIPTION

[0038] The glass composition according to the present invention is at least a quaternary system. The glass composition comprises about 50 mol% to about 95 mol% of B2O3; and about 5 mol% to about 50 mol% of one or more glass components selected from the group consisting of: Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO and ZnO. The glass composition comprises less than 30 mol% of Rb2O. The glass composition according to the present invention degrades under physiological conditions and loses at least 5% by mass within 24 hours when exposed to a buffered saline solution.

[0039] The glass composition is a particulate material comprising particles having a size of about 1 to about 50 μm. The glass composition comprises at least some particles having a size configured to block the dentinal tubules, thereby desensitizing the dentin. In the context of the present invention, particles having a size configured to block the dentinal tubules should be understood to mean that the particles are located in or on the dentinal tubules, thereby reducing the movement of the dentinal fluid.

[0040] In the context of the present invention, a glass composition that is "at least a quaternary system" should be understood to mean a glass having four or more different elements. For example, a glass composition consisting only of B2O3, Li2O and ZnO would be considered a quaternary system, since the glass contains the elements boron, lithium, zinc and oxygen. Similarly, a glass composition consisting only of B2O3, CaO and CaF2 would be considered a quaternary system, since the glass contains boron, calcium, fluorine and oxygen. In contrast, a glass composition consisting only of B2O3 and Na2O would be considered a ternary system, since the glass contains boron, sodium and oxygen.

[0041] It should be understood that "about 5 mol% to about 50 mol% of one or more glass components" refers to the total mole percentage of the glass components, rather than the mole percentage of each individual component. For example, the glass composition according to the present invention may include 2.5 mol% of Li2O and 2.5 mol% of ZnO to provide the 5 mol% of additional glass components.

[0042] It should be understood that "about X mol%" refers to any value within ±2% of the reported percentage. For example, "about 10 mol%" refers to values ​​from 8 mol% to 12 mol%, because all of these values ​​will be within the reported ±2% range of 10%; "about 50 mol%" refers to values ​​from 48 mol% to 52 mol%, because all of these values ​​will be within the reported ±2% range of 50%.

[0043] It should be understood that in the description of particle size, "about X μm" is determined based on the ASTM acceptable tolerance of the test sieve according to the size. For example, the acceptable tolerance for the 50 μm test sieve is 3 μm. Therefore, "about 50 μm" refers to particles with a size of 47 μm to 53 μm. In another example, the acceptable tolerance for the 35 μm test sieve is 2.6 μm. Therefore, "about 35 μm" refers to particles with a size of 32.4 μm to 38.6 μm. The ASTM acceptable tolerance for the 25 μm test sieve is 2.2 μm. For test sieves without standard acceptable tolerances (e.g., test sieves below 20 μm), "about X μm" means ±15% of the size of 5 to 15 μm, and ±50% of the size of less than 5 μm. For example, "about 1 μm" refers to particles with a size of 0.5 to 1.5 μm.

[0044] Glass composition

[0045] Glass composition according to the present invention can include fluoride source, for example, CaF2, NaF, Na2PO3F, KF or SnF2. Fluoride included in glass composition can cause fluoride to be discharged when glass is degraded. The released fluoride can form fluorapatite (Ca5(PO4)3F) in or around dentinal tubules, which can form protective precipitate and further reduce dentin sensitivity. In glass composition including fluoride, fluoride source can account for up to 30mol% of glass composition. In some examples, fluoride source can be about 1mol% to about 10mol% of glass composition, for example, about 1mol% to about 5mol%. In specific examples, fluoride source accounts for about 15mol% of described composition. Compared with the composition using NaF, Na2PO3F or KF, for every mole of raw material, the composition including CaF2 or SnF2 provides twice the fluorine content.

[0046] In some examples, the glass composition includes about 1 mol % to about 10 mol % of fluoride. In some examples, the glass composition includes about 1 mol % to about 5 mol % of fluoride.

[0047] In some examples, the glass composition comprises sufficient fluoride such that 0.1 g of the particulate material releases fluoride into 10 mL of a buffered saline solution at an average rate of about 1 ppm / hour to about 15 ppm / hour over 1, 2, 4, 8, 12, 18, or 24 hours. In the context of the present invention, ppm is measured as mass / mass. In a specific example, the glass composition comprises sufficient fluoride such that about 4 ppm to about 6 ppm of fluoride is released per hour over a period of more than 1 hour.

[0048] In some examples of glass compositions according to the present disclosure, less than 20 mol %, eg, less than 15 mol %, less than 10 mol %, or less than 5 mol % of the glass composition is CaO, MgO, and Na2O.

[0049] In an example of the glass composition according to the present invention, the glass composition does not contain any CuO; and includes less than 0.1 mol% BaO and less than 0.1 mol% P2Os. In a specific example, the glass composition does not contain any CuO, BaO or P2O5.

[0050] The glass composition according to the present invention may include about 5 mol % to about 50 mol % of one or more glass components selected from the group consisting of Li2O, Rb2O, K2O, Na2O, SrO and ZnO; and wherein the glass composition includes less than 0.1 mol % of CaO and less than 0.1 mol % of MgO.

[0051] The glass composition according to the present invention may include about 5 mol % to about 50 mol % of one or more glass components selected from the group consisting of Li2O, Rb2O, K2O, Na2O, SrO and ZnO; and wherein the glass composition includes less than 0.1 mol % of CaO, less than 0.1 mol % of MgO and less than 0.1 mol % of Na2O.

[0052] The glass composition according to the present invention may include about 50 mol % to about 80 mol % B 2 O 3 , for example, about 50 mol % B 2 O 3 .

[0053] The glass composition according to the present invention may contain about 5 mol % to about 40 mol %, for example, about 20 mol % to about 40 mol %, of one or more glass components selected from the group consisting of Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO and ZnO.

[0054] The glass composition according to the present invention may include B2O3, LiO and ZnO, and optionally Rb2O, Na2O and / or a fluoride source. In a specific example, the glass composition includes: about 5 mol% to about 25 mol% of Li2O and about 5 mol% to about 25 mol% of Rb2O; and / or about 5 mol% to about 25 mol% of Li2O, and about 5 mol% to about 15 mol% of ZnO, and optionally about 5 mol% to about 15 mol% of Na2O. The glass composition may contain about 50 mol% of B2O3 or about 70 mol% of B2O3.

[0055] The glass composition according to the present invention may include B2O3 and ZnO, and optionally Rb2O and / or a fluoride source. In a specific example, the glass composition includes: about 5 mol% to about 30 mol% ZnO. If present, the content of RbO2 may be about 5 mol% to about 30 mol%. The glass composition may include about 50 mol% B2O3.

[0056] The glass composition according to the present invention may include B2O3 and SrO, and optionally ZnO and / or a fluoride source. In a specific example, the glass composition includes: about 5 mol% to about 30 mol% SrO. If present, about 5 mol% to about 30 mol% ZnO may be included. The glass composition may include about 50 mol% B2O3.

[0057] As described above, the present invention also provides a glass composition, comprising: a fluoride, wherein the fluoride is about 5 mol % to about 10 mol % of CaF2, SnF2, NaF, KF or any combination thereof; and about 90 mol % to about 95 mol % of a combination of B2O3, Na2O, MgO and CaO; wherein the boron, magnesium, a combination of Na and any K, and a combination of Ca and any Sn in the glass composition are present in an element ratio of about 20: about 4: about 6: about 3, respectively.

[0058] A specific example of such a glass composition includes: about 50 mol% B2O3, about 15 mol% Na2O, about 20 mol% MgO, about 10 mol% CaO, and about 5 mol% CaF2. This composition may be referred to herein as composition "PBF1".

[0059] Another specific example of such a glass composition includes: about 48 mol% B2O3, about 9 mol% Na2O, about 19 mol% MgO, about 14 mol% CaO, and about 10 mol% NaF. This composition may be referred to herein as the composition "PBF1-Na".

[0060] Particle size distribution

[0061] The glass composition according to the present invention is a particulate material including particles having a size of about 1 μm to about 50 μm. At least some of the particles are sized so as to be located in or on top of the dentin tubules. The diameter of the dentin tubules varies naturally and the size is mainly about 0.5 μm to about 8 μm, for example, about 0.5 to about 5 μm. Therefore, the glass composition of the present invention can be used to desensitize dentin, which can temporarily relieve the pain associated with sensitive teeth.

[0062] In some examples, at least 75% of the particles comprising the granular material are smaller than 50 μm in size. In other examples, at least 85% or at least 95% of the particles are smaller than 50 μm in size. In some examples, at least 5% of the particles comprising the granular material are smaller than 7 μm in size.

[0063] In a specific example, the particulate material consists of a plurality of particles, wherein at least 5% of the particles have a size less than 35 μm, at least 5% of the particles have a size less than 15 μm, and at least 5% of the particles have a size less than 7 μm.

[0064] In a specific example, the particulate material is composed of a plurality of particles, wherein at least 5% of the particles have a size of about 15 μm to 35 μm, at least 5% of the particles have a size of about 6 μm to about 15 μm, and at least 5% of the particles have a size of about 3 μm to about 7 μm.

[0065] In some embodiments, the particulate material consists of a plurality of particles, wherein the particle size distribution is about 5 μm D×10, about 15 μm D×50, and about 30 μm D×90.

[0066] degradation

[0067] The glass composition according to the present invention degrades under physiological conditions, and when exposed to a buffered saline solution, the glass composition according to the present invention loses at least 5% by mass within 24 hours. In some examples, when exposed to a buffered saline solution, the glass composition may lose at least 20% by mass, at least 40% by mass, at least 60% by mass, or at least 80% by mass within 24 hours.

[0068] Dentin desensitizing composition

[0069] The glass composition according to the present invention may be formulated in a dentin desensitizing composition comprising an anhydrous orally compatible carrier. The dentin desensitizing composition according to the present invention does not contain water because the glass composition would degrade if exposed to water.

[0070] In the context of the present invention, "anhydrous" is understood to mean that the dentin desensitizing composition contains very little water, so that the glass composition is still able to reduce dentin sensitivity over the expected life. The expected life of the product refers to the maximum expected time between when the dentin desensitizing composition is produced and when the dentin desensitizing composition is completely consumed or disposed of.

[0071] The orally compatible carrier for the dentin desensitizing composition can be a mouthwash; a carrier formulated to be mixed with other ingredients to form a mouthwash; or an orally compatible viscous carrier such as toothpaste, tooth gel, preventive paste, tooth varnish; or a carrier formulated to be mixed with other ingredients to form a toothpaste. The orally compatible viscous carrier can have a viscosity of about 100 cP at 30°C to about 150000 cp at 30°C.

[0072] The dentin desensitizing composition may include a glass composition according to the present invention, as described above, comprising fluoride, wherein the amount of the glass composition is sufficient so that the desensitizing composition comprises from about 100 ppm to about 5000 ppm of fluoride.

[0073] An example of a dentin desensitizing composition according to the present invention is a toothpaste comprising a glass composition according to the present invention and: an abrasive; a cleaning agent such as sodium lauryl sulfate; a fluoride source; an antibacterial agent; a flavoring agent; a remineralizing agent; a sugar alcohol such as glycerol, sorbitol or xylitol; an additional dentin desensitizing agent; a hydrophilic polymer such as polyethylene glycol; or any combination thereof. The glass composition may be about 0.5% to about 15% by mass of the toothpaste.

[0074] A specific example of a dentin desensitizing composition according to the present invention is a toothpaste comprising the glass composition according to the present invention and: glycerol, silicon dioxide, polyethylene glycol (eg, PEG 400), titanium dioxide, carbomer and a sweetener (eg, acesulfame potassium or saccharin sodium).

[0075] Another example of a dentin desensitizing composition according to the present invention is a toothpaste comprising the glass composition according to the present invention and: α-carbomer, DL-limonene, glycerin, mint flavor, polyethylene glycol (e.g., PEG-8), silicon dioxide, titanium dioxide, sodium lauryl sulfate and a sweetener (e.g., acesulfame potassium or saccharin sodium).

[0076] Another example of a dentin desensitizing composition according to the present invention is a carrier comprising the glass composition according to the present invention, wherein the carrier is formulated to be mixed with other components to form a toothpaste.

[0077] Another example of the dentin desensitizing composition according to the present invention is a carrier that is formulated to be mixed with other components to form a mouthwash. The specific example of the carrier includes a glass composition according to the present invention and: anhydrous alcohol, cetylpyridinium chloride, chlorhexidine, essential oils, benzoic acid, poloxamer, sodium benzoate, spices, coloring agents or any combination thereof. Other components that can be mixed with the carrier to form a mouthwash can include: water, peroxide, cetylpyridinium chloride, chlorhexidine, essential oils, alcohol, benzoic acid, poloxamer, sodium benzoate, spices, pigments or any combination thereof. The carrier and other components can be stored in separate compartments and mixed together before the mixture is used as a mouthwash. The separated compartments can be in the form of a multi-chamber bottle, for example, a bifurcated bottle.

[0078] Another example of a dentin desensitizing composition according to the present invention is a preventive paste (also referred to as a "preventive paste") comprising the glass composition according to the present invention. Specific examples of intended preventive pastes include the glass composition according to the present invention and: pumice, glycerin, diatomaceous earth (preferably fine sand), sodium silicate, methyl salicylate, sodium dihydrogen phosphate, sodium carboxymethylcellulose, sweeteners (such as acesulfame potassium or saccharin sodium), flavors, pigments, or any combination thereof.

[0079] method

[0080] The glass composition according to the present invention can be synthesized by the following method: mixing appropriate molar amounts of raw materials; charging the precursor mixture into a platinum crucible (Johnson Matthey, Noble Metals, Pennsylvania); placing the filled crucible in a furnace (Carbolite, RHF 1600) at room temperature; heating the furnace (e.g., at a rate of 25°C / min) to an initial soak temperature of 600°C; maintaining the temperature for 60 minutes; increasing the temperature (e.g., at a rate of 20°C / min) to a soak temperature of 1100°C; maintaining the temperature for 60 minutes; and quenching the glass melt between two stainless steel plates.

[0081] It should be understood that the specific heating rates, times and temperatures disclosed above can be varied as long as the glass is molten. The heating rate is 10 to 20 degrees per minute and the holding temperature can remove at least some bubbles from the glass.

[0082] The obtained quenched glass can be ground / milled separately in a planetary micromill (Pulverisette 7, Fritsch, Germany) and sieved with an ASTM E-11 compatible sieve (Cole Palmer, USA) to obtain particles smaller than 25 μm. The glass can be stored in glass scintillation vials under vacuum.

[0083] Although the obtained glass composition includes oxides, the starting reagents may include oxides, carbonates, or both. For example, the starting reagents may include boron oxide, rubidium carbonate, lithium carbonate, and calcium fluoride. Rubidium carbonate and lithium carbonate decompose in a furnace to release CO2, generating their corresponding oxides.

[0084] The particle size was measured using a Malvern Mastersizer (MS) 3000 laser diffraction particle size analyzer. The glass powders were suspended in deionized water so that the darkness of the suspension was between 5 and 8%. The suspension was measured using a blue (l = 470 nm) and a red (l = 632.8 nm) laser for 5 measurements (n = 5).

[0085] By placing 0.1 g of the glass composition in 10 ml of TRIS buffered saline (BioUltra, Sigma Aldrich, Canada) in a 15 ml Falcon tube. The solution was stirred at 120 rpm and maintained at a temperature of 37°C for the desired release time, for example, 1, 3, 6, 12 or 24 hours. After completion, the liquid portion was poured out and filtered using a 0.22 μm filter (Canadian Sastedt syringe filter) into a new, clean 15 ml Falcon tube, which was capped and then stored at 4°C until fluoride quantification. Use an electrode equipped with a fluoride combination AB250 pH / ion selective electrode instrument The concentration of released fluoride was quantified. Standard solutions were prepared using a fluoride analysis standard solution (NaF, 0.1 MF, Sigma-Aldrich, Canada) specifically for ion-selective electrodes, and calibration curves were obtained prior to analysis. Liquid extracts extracted from the extracts of each composition were prepared for ion analysis according to the electrode manufacturer's instructions. Ion concentrations are reported as the mean of n=3 ± SD.

[0086] In the context of the present invention, the mass loss of the glass composition is associated with a solid glass cylinder having a length of 6 mm and a diameter of 4 mm. The glass cylinders were prepared as described above by making molten glass and quenching the molten glass in a stainless steel mold (6 mm long x 4 mm in diameter) disposed between two stainless steel plates. The excess glass on the cylinder was carefully etched away by a Speedy Sharp tool and the remaining excess glass was removed (while being placed back into the stainless steel mold) using a grinding / polishing wheel with 240 grit sandpaper and applying pressure to the mold / glass on the wheel. Glass cylinders with uneven edges, bubbles or debris were excluded.

[0087] Use three cylinders to measure the mass loss of a given glass composition. Measure and record the length and diameter of each cylinder 3 times (changing the position of the measurement each time), and record as the mean ± SD. Measure the mass of each cylinder separately (Sartorius Cubis, Model MSU-224S100Dl, Cole Palmer (Sartorius Cubis, Model MSU-224S100DI, Cole Palmer). The three cylinders are placed in 50mL falcon tubes, each tube is filled with 20mL of TRIS buffered saline (BioUltra, Sigma Aldrich, Canada). The test tubes are then placed in a 37°C shaking incubator (Thermos Scientific, MaxQ 4000) and stirred at 120rpm for 24 hours. After 24 hours, the cylinders are filtered out of the solution, rinsed with cold distilled H2O, and then dried overnight in an oven at 37°C. Once dry, measure its length, diameter and mass.

[0088] The wear resistance of the composition is determined by measuring the gloss and surface roughness of the resin composite or enamel surface after brushing with the composition. ESPE Filtek Supreme Ultra Universal Restorative, shade A2B (ESPEFiltek Supreme Ultra Universal Restorative, shade A2B) (3M, St. Paul, Minnesota, USA) is cured in a metal combination mold with a diameter of 12.7 mm and a thickness of 2 mm. Mylar sheets are placed above and below the mold, and glass plates are used to press the composite material flat and squeeze out excess material. A broadband multi-wave LED light curing device (ValoGrand, Ultradent Products, South Jordan, Utah, USA) is placed directly on top of the sample and cured for 20 seconds at standard settings. Excess material is removed by hand before mounting the sample for brushing.

[0089] The samples were stored in the dark at 37 °C for at least 24 h before use. The surface of the enamel samples was prepared by polishing with different levels of grit to produce a flat and smooth surface. The initial flat surface was sanded with low-grit sandpaper (Klingspor P800C, Haig, Germany), followed by polishing with increasing amounts of grit. The final polishing step was performed on a 3 μm cloth pad and then with a 0.3 μm aluminum oxide powder slurry (Buehler, Inc., Lake Bluff, IL, USA). Each polishing step was performed for about 1 min with pressure applied by hand.

[0090] A custom-made brushing machine (Ultradent, South Jordan, Utah, USA) simulates the brushing action of 10 samples simultaneously. It is equipped with a toothbrush (GUM brand 459PC, Sunstar, Guelph, Ontario, Canada), and a constant load of 176g is applied during the brushing process. The toothbrush is replaced after 10,000 brushing cycles. During brushing, the sample is covered with a toothpaste slurry with a weight ratio of 5:8 with distilled water of at least 3 mm. Every 2,500 brushing cycles, the sample is rotated to a different position (ensuring that the same toothpaste is used to brush the teeth each time the sample is moved). 20,000 brushing cycles represent approximately 2 years of brushing time. The repetition and position of the toothpaste in the machine are randomly assigned by a random number generator (for each substrate), while manually ensuring that the same toothpaste is repeated at least twice in one run to ensure that the toothbrush rotates.

[0091] A gloss meter (Novo-Curve G, Rhopoint Instruments, Hastings, UK) was used to measure the gloss of composite and enamel surfaces. Gloss was measured at three random points to create a surface average. Traceable calibration plates with high and low reflectivity were used daily to verify the gloss meter calibration. The gloss was measured at 0, 5000, 10000, 15000 and 20000 brushing cycles, and a new toothpaste slurry was used after measuring the gloss.

[0092] The average roughness of the surface was also measured before brushing and after 20,000 brushing cycles. An atomic force microscope (nGauge, version 1.0, ICSPI, Waterloo, Ontario, Canada) was used to measure the average roughness at three different locations to form an average value for the surface. An area of ​​25×25 μm was scanned at a speed of 1200 μs / pixel. The data were analyzed using Gwyddion (http: / / gwyddion.net) software.

[0093] Example

[0094] The glass compositions shown in Table 1 are all synthesized in the following manner: Weigh a determined amount of analytically pure reagents (boron oxide, rubidium carbonate, lithium carbonate and calcium fluoride) (Sigma Aldrich, Canada). Each formulation is mixed for 60 minutes to ensure uniformity. Each precursor mixture is placed and filled in a 50mL platinum crucible (Zheng Xin Matthey Group, Pennsylvania Precious Metals Company). The filled crucible is then placed in a furnace (Jiabaolai, RHF 1600) at room temperature. The furnace is heated (25°C / min) to an initial holding temperature of 600°C and maintained for 60 minutes. The temperature is then raised (20°C / min) to a final holding temperature of 1100°C and maintained for 60 minutes. When pouring out, each glass melt is quenched between two stainless steel plates. The resulting quenched glass is ground / milled separately in a planetary micro-mill (Pulverisette 7, Germany) and sieved with an ASTM E-11 compatible sieve (Cole Parmer, USA) to obtain particles less than 25μm.

[0095] Glass Logo <![CDATA[B2O3(mol%)]]> <![CDATA[Li2O(mol%)]]> <![CDATA[Rb2O(mol%)]]> <![CDATA[CaF2(mol%)]]> BCF100 70 20 10 0 BCF101 70 20 9 1 BCF102 70 20 8 2 BCF103 70 20 7 3 BCF104 70 20 6 4 BCF200 70 10 20 0 BCF201 70 9 20 1 BCF202 70 8 20 2 BCF203 70 7 20 3 BCF204 70 6 20 4

[0096] Table 1. Exemplary glass compositions according to the present invention

[0097] Table 2 shows the particle size distribution of the exemplary glasses of Table 1.

[0098] Glass Logo D×(10) D×(50) D×(90) BCF100 5.16 14.5 29.7 BCF101 4.23 11.9 25 BCF102 4.77 13.8 29.1 BCF103 4.75 13.6 28.4 BCF 104 3.97 12.7 28.3 BCF200 6.87 15.1 27.6 BCF201 6.31 16.2 31.7 BCF202 6.5 16.9 32.5 BCF203 6.22 16.5 32.4 BCF204 6.35 17 33.6

[0099] Table 2. Particle size distribution (pm)

[0100] It should be understood that "Dx(#)" refers to the percentage of particles with a size smaller than the stated value. For example, BCF100 has a Dx(10) of 5.16 microns, which means that 10% of the particles have a size smaller than 5.16 microns.

[0101] Particles of the exemplary glasses of Table 1 were evaluated for fluoride release over 12 hours and 24 hours in a buffered saline solution using the method described above. Table 3 lists the ppm of fluoride released.

[0102] Glass Logo Fluoride release - 12 hours (ppm) Fluoride release - 24 hours (ppm) BCF100 0 0 BCF101 32 31 BCF102 59 58 BCF103 69 77 BCF104 65 70 BCF200 0 0 BCF201 24 23 BCF202 48 47 BCF203 62 59 BCF204 76 71

[0103] Table 3. Average fluoride release (ppm) at 12 and 24 hours.

[0104] BCF201 was formulated into two toothpastes to test the abrasive effects of glass particles and compared with Sensodyne TM Whitening, repair and Protect TM Toothpaste ("Sensodyne") and Colgate TMThe exemplary glasses were formulated with: (a) Colgate TM Enamel HealthSensitivity Relief TM (Colgate-Palmolive, Toronto, Ontario, Canada) ("Colgate EN"); or (b) Gel 7 HT (Germiphene, Brantford, Ontario, Canada) ("Gel"), a neutral pH fluoride gel dentifrice that does not contain any abrasive materials.

[0105] In the following table and Figures 1 to 10 The results of the abrasive test are illustrated in Table 4. Table 4 shows the gloss units of the resin composite surface after different brushing cycles using different toothpastes. Table 5 shows the gloss units of the resin composite after different brushing cycles using different toothpastes. Table 6 shows the roughness of the resin composite surface after 20,000 brushing cycles using different toothpastes.

[0106] Table 7 shows the roughness of tooth enamel surface after 20,000 brushing cycles using different toothpastes.

[0107]

[0108] Table 4. Gloss units of resin composite surfaces with different brushing times

[0109]

[0110] Table 5. Gloss units of tooth enamel surface after different numbers of brushing cycles

[0111]

[0112] Table 6. Roughness of the resin composite surface after 20,000 brushing cycles

[0113]

[0114] Table 7. Roughness of tooth enamel surface after 20,000 brushing cycles

[0115] Additional exemplary glass compositions according to the present invention, as well as glass compositions that are not examples of the present invention, are shown in Table 8, which shows the mole percentages of the various components.

[0116]

[0117]

[0118]

[0119] Table 8.

[0120] The exemplary glass compositions shown in Table 8 and other compositions were selected according to Design of Mixtures (Design Expert 8.0.4 by Stat-Ease Inc.) to evaluate the effects of various ranges of components on the glass composition.

[0121] Glass compositions were synthesized as described above. Briefly, sufficient amounts of analytical grade reagents (Sigma Aldrich, Canada) needed to form each of the above compositions were weighed. Each formulation was mixed for 60 minutes to ensure uniformity. Each precursor blend was placed and filled in a 50 mL platinum crucible (Johnson Matthey Group, Pennsylvania Precious Metals). The filled crucible was then placed in a furnace (Jiabaolai, RHF 1600) at room temperature. The furnace was heated (25°C / min) to an initial holding temperature of 600°C and maintained for 60 minutes. The temperature was then raised (20°C / min) to a final holding temperature of 1100°C and maintained for 60 minutes. When poured out, each glass melt was quenched between two stainless steel plates.

[0122] The following compositions are specific examples of compositions that form glasses under the above-described quenching conditions, which represent one selection of standard quenching conditions suitable for large-scale production processes.

[0123] Glass Logo <![CDATA[B2O3]]> <![CDATA[Li2O]]> <![CDATA[RbO2]]> <![CDATA[Na2O]]> SrO ZnO <![CDATA[CaF2]]> NaF KF <![CDATA[SnF2]]> BCF301 50 23.2 0 0 0 0 26.8 0 0 0 BCF308 50 0 0 0 0 24.3 0 0 25.7 0 BCF313 50 25.4 0 0 0 0 0 0 24.6 0 BCF315 50 24.2 25.8 0 0 0 0 0 0 0 BCF320 50 0 24.9 0 0 25.1 0 0 0 0 BCF321 50 0 0 0 25.2 0 24.8 0 0 0 BCF322 50 25.2 0 0 0 0 0 24.8 0 0 BCF324 50 0 0 0 0 20.0 30.0 0 0 0 BCF342 50 0 0 0 0 25.9 0 24.1 0 0 BCF357 50 0 0 0 24.9 25.1 0 0 0 0 BCF364 50 11.0 0 13.1 0 11.6 10.5 3.8 0 0

[0124] Table 9 - Examples of compositions that form glasses under the described quenching conditions For the exemplary compositions listed in Table 9, the resulting quenched glasses have the following bulk properties:

[0125]

[0126] Table 10. Bulk properties of some exemplary glasses

[0127] The obtained exemplary quenched glasses listed in Table 9 were respectively ground / milled in a planetary micro-pulverizer (Pulverisette 7, Germany), and sieved with a sieve conforming to ASTM E-1 1 (Cole Parmer, USA) to obtain particles smaller than 25 μm.

[0128] The particle size distributions of the exemplary glasses listed in Table 9 are listed in Table 9. BCF315, BCF326 degraded too quickly in deionized water to obtain accurate particle size measurements.

[0129] Glass Logo D×(10) D×(50) D×(90) BCF301 3.15 11.00 24.30 BCF308 3.07 9.71 22.10 BCF313 4.70 11.00 21.00 BCF315 * * * BCF320 3.11 9.23 20.60 BCF321 2.94 9.73 20.70 BCF322 3.96 10.40 21.10 BCF324 3.63 9.39 19.80 BCF342 3.36 10.90 24.30 BCF357 2.79 9.66 21.90 BCF364 2.9 8.73 19.8

[0130] Table 11 - Particle size distribution (μm)

[0131] The particles of the exemplary glasses listed in Table 9 were evaluated for mass loss and fluoride release in buffered saline solutions at 1, 4 and 24 hours. Samples were prepared in 15 mL conical test tubes (n=3), weighed and recorded. 0.1 grams of each glass powder (<25 microns) was weighed and placed in 10 mL of TRIS buffered saline (BioUltra, Sigma Aldrich, Canada) in a weighed 15 mL Falcon tube. The test tubes were sealed with parafilm and then placed in a shaking incubator at 37°C and stirred at 120 rpm for four separate time points: 5 minutes, 30 minutes, 1 hour, 3 hours, 24 hours and 48 hours. After the specified time points had passed, the test tubes were removed from the incubator and the solution was immediately centrifuged (Eppendorf, Centrifuge 5702) at a speed of 3.0 RCF / 4.4 RPM for 15 minutes. The supernatant was poured into a fresh 15 mL Falcon tube. Additionally, a sample of the 48 hour incubation powder was resuspended in 10 mL of fresh TRIS buffered saline by vortex mixing and allowed to incubate for an additional 8 hours (56 hours total incubation). The re-incubated powder was treated in the same manner as the other samples. The particles were dried in separate Falcon tubes in an oven at 50°C.

[0132] The release of fluoride ions was measured using an Accumet AB250 pH / ion selector equipped with a fluoride electrode (Fisher Scientific). To calibrate the probe, six standard solutions were prepared using a fluoride analysis standard solution (NaF, 0.1F, Sigma Aldrich, Canada) specifically for ion-selective electrodes. Using TRIS buffered salt (BioUltra, Sigma Aldrich, Canada) as a solvent, the fluoride concentrations of the synthesized standards were: 1000ppm, 100ppm, 10ppm, 1ppm, 0.1ppm and 0.01. Prior to calibration (according to the manufacturer's instructions), TISAB concentrate (4.5mL) was added to each standard solution. Once the probe was calibrated, the standard slope was checked to ensure that it was within the instructions for use. TISAB concentrate (1.0mL) was added to the decanted supernatant, and its fluoride concentration was then measured using a calibrated probe. Ion concentrations are reported as mean ± SD.

[0133] The mass loss and ppm of released fluoride are shown in Table 12. BCF314 was completely degraded in the buffered saline solution before the 1 hour time point, without the inclusion of any fluoride source.

[0134]

[0135] Table 12. Mass loss and fluoride release of exemplary glasses at 1, 4, and 24 hours

[0136] The compositions listed in Table 8 reflect the design space. The results of the tested compositions provide the following equations, which can allow relative comparisons of different compositions; and / or which can be used to identify trends associated with different components of the compositions. Although experimental and modeling errors prevent absolute predictions of glass properties, these equations can be used to guide and refine glass composition designs. When used together, these models can help suggest which factors can be weighed in the tailored design of multi-component compositions within the tested composition space. In the following equations, the values ​​of the listed components are expressed as percentages (not fractions or decimals). For example, 50 mol% B2O3 means "50" (not "0.5").

[0137] Glass is generally expected to form under the quench conditions tested if the following equation is less than or equal to 1.60:

[0138] (2.01*e y +0.99) / (1+e y )

[0139] Among them, y=-0.086622*[B2O3]+0.14169*[Li2O]-0.565849*[ZnO]+0.192175*[Na2O]-0.461537*[CaF2]+0.036 636*[KF]+0.00365*[NaF]+0.191201*[SnF2]+0.192612*[RbO2]+0.199999*[SrO]+0.01393*[B2O3]*[ZnO ]+0.012239*[B2O3]*[CaF2]-0.012412*[Li2O]*[CaF2]-0.013904*[Li2O]*[RbO2]-0.010857*[ZnO]*[Ca F2]-0.013296*[ZnO]*[RbO2]-0.010699*[ZnO]*[SrO]+0.010128*[CaF2]*[KF]-0.012103*[CaF2]*[SrO].

[0140] The density of glass is usually predicted using the following equation:

[0141] ρ=0.018783*[B2O3]+0.026444*[Li2O]+0.046191*[ZnO]+0.033814*

[0142] [Na2O]+0.039196*[CaF2]+0.026997*[KF]+0.029458*[NaF]+0.049441*[SnF2]+0.047057*[Rb O2]+0.054984*[SrO]. The glass density is about 1.3g / cm 3 To about 2.2g / cm 3 It is particularly useful for non-aqueous oral care formulations. The main liquid and solid components of non-aqueous toothpaste, glycerin and silicon dioxide, have 1.3 g / cm 3 To about 2.2g / cm 3 density.

[0143] The glass transition temperature (T) can usually be predicted using the following formula: g ):

[0144] T g =3.49398*[B2O3]+3.66342*[Li2O]+6.38755*[ZnO]+6.23689*[Na2O]+

[0145] 6.43079*[CaF2]+3.31695*[KF]+5.04074*[NaF]+9.88761*[SnF2]+3.29777*[RbO2]+10.51264*[SrO]. It should be understood that phase separated glasses may experience multiple glass transitions, and the magnitude of their glass transitions is not necessarily representative of the volume distribution of the phases. Although the above equation predicts the onset of the glass transition, if phase separation occurs, the predicted onset may not be the major glass transition of the composition. Therefore, the predicted glass transition temperature may be significantly different from the measured major glass transition temperature.

[0146] The equation relating the percent mass loss after 1 hour under the test conditions is:

[0147] (100*e y ) / (1+e y )

[0148] Where y = 0.088098*[B2O3] + 0.062481*[Li2O] - 0.262486*[ZnO] + 0.055442*[Na2O] - 0.165517*[CaF2] + 0.089171*[KF] + 0.075875*[NaF] + 0.10439*[SnF2] + 0.109897*[RbO2] - 0.089987*[SrO]. The above equation is highly predictive for identifying glass compositions that show complete dissolution under the test conditions within 1 hour and can be used to identify other glasses that degrade within this time frame. In addition, while the equation does not provide an accurate estimate of mass loss for slower degrading compositions, the equation may be useful for predicting relative changes in degradation that can be expected to occur with changes in composition. Such relative changes can be used as a guide in the design of glass compositions.

[0149] The equation relating the amount of fluoride released (in ppm) after 1 hour under the test conditions is:

[0150] (2750*e y ) / (1+e y )

[0151] Where y = -0.05785*[B2O3]-0.158337*[Li2O]-0.170872*[ZnO]-0.184773*[Na2O]+0.05638*[CaF2]+0.101381*[KF]+0.053886*[NaF]-0.307462*[SnF2]-0.183034*[RbO2]-0.184126*[SrO]. Although the above equation does not provide an accurate estimate of the amount of fluoride released for all glass compositions, the model can still be used to predict relative changes in fluoride release that will occur with changes in composition.

[0152] PBF1 was synthesized in the following manner: 11.60 g of B2O3, 5.30 g of Na2CO3, 2.69 g of MgO, 3.33 g of CaCO3 and 0.7 g of CaF2 (Sigma Aldrich, Canada) were weighed. The raw materials were mixed for 60 minutes to ensure uniformity. The blend was placed and filled in a 50 mL platinum crucible (Zhengxin Matthey Group Precious Metals, Pennsylvania). The filled crucible was then placed in a furnace (Jiabaolai, RHF 1600) at room temperature. The furnace was heated (25 ° C / min) to an initial holding temperature of 600 ° C and kept for 60 minutes. The temperature was then raised (20 ° C / min) to a final holding temperature of 1200 ° C and kept for 60 minutes. When poured out, the glass melt was quenched between two stainless steel plates. The obtained quenched glass was ground / milled in a planetary micromill (Pulverisette 7, Germany) and sieved with a sieve conforming to ASTM E-11 (Cole Parmer, USA) to obtain particles smaller than 25 μm.

[0153] Comparative glass compositions (referred to as Comparative Examples (CE) 1 and 2) were similarly synthesized using 5.80 g of B2O3, 23.66 g of P2O5, 5.30 g of Na2CO3, 1.34 g of MgO, 6.67 g of CaCO3, and 0.70 g of CaF2 to yield: CE1 contained about 25 mol% B2O3, about 25 mol% P2O5, about 15 mol% Na2O, about 10 mol% MgO, about 20 mol% CaO and about 5 mol% CaF2; and 5.80 g of B2O3, 23.66 g of P2O5, 7.07 g of Na2CO3, 1.34 g of MgO, 5.00 g of CaCO3 and 0.70 g of CaF2, and CE2 containing about 25 mol% B2O3, about 25 mol% P2O5, about 20 mol% Na2O, about 10 mol% MgO, about 15 mol% CaO and about 5 mol% CaF2.

[0154] Use the 1cm 3 The density of the glass powder was measured using an AccuPyc 1340 helium pycnometer (Micromeritics, USA) with an insert. Before use, a volume of 0.718512 cm 3 The pycnometer is calibrated with a standard solution of . For glass analysis, the insert is loaded with about 0.5 g to 0.7 g of glass powder. Three samples of each glass are measured, and each measurement is the average of 10 readings.

[0155] The measured density of PBF1 is 2.5951±0.0072 g / cm 3The density of CE1 was measured to be 2.7079±0.0021 g / cm 3 The density of CE2 was measured to be 2.6749±0.0013 g / cm 3 .

[0156] Fluoride release and mass loss of PBF1, CE1 and CE2 were measured. Samples (n=3) were prepared in 15 mL conical test tubes, weighed and recorded. 0.1 g of each glass powder (<25 microns) was weighed and placed in 10 ml of TRIS buffered saline (BioUltra, Sigma Aldrich, Canada) in a 15 ml Falcon tube. The test tube was sealed with parafilm and then placed in a shaking incubator at 37°C and stirred at 120 rpm for four separate time points: 5 minutes, 30 minutes, 1 hour, 3 hours, 24 hours and 48 hours. After the specified time point has passed, the test tube was removed from the incubator and the solution was immediately centrifuged at 3.0 RCF / 4.4 RPM (Eppendorf, Centrifuge5702) for 15 minutes. The supernatant was poured into a fresh 15 mL Falcon tube. Additionally, a sample of the 48 hour incubation powder was resuspended in 10 mL of fresh TRIS buffered saline by vortex mixing and allowed to incubate for an additional 8 hours (56 hours total incubation). The re-incubated powder was treated in the same manner as the other samples. The particles were dried in separate Falcon tubes in an oven at 50°C.

[0157] The release of fluoride ions was measured using an Accumet AB250 pH / ion selector equipped with a fluoride electrode (Fisher Scientific). To calibrate the probe, six standard solutions were prepared using a fluoride analysis standard solution (NaF, 0.1F, Sigma Aldrich, Canada) specifically for ion-selective electrodes. Using TRIS buffered saline (BioUltra, Sigma Aldrich, Canada) as a solvent, the concentrations of sodium fluoride in the synthesized standard solutions were: 1000ppm, 100ppm, 10ppm, 1ppm, 0.01ppm and 0.001. Prior to calibration (according to the manufacturer's instructions), TISAB concentrate (4.5mL) was added to each standard solution. Once the probe was calibrated, the standard slope was checked to ensure that it was within the instructions for use. TISAB concentrate (1.0mL) was added to the decanted supernatant, and its fluoride concentration was then measured using the calibrated probe. Ion concentrations are reported as mean ± SD.

[0158] The amount of fluoride ions released by PBF1 was measured to be 89±2 ppm at 5 minutes, 94±3 ppm at 30 minutes, 105±5 ppm at 1 hour, and 94±7 ppm at 3 hours. No measurable fluoride ions were released by CE1 or CE2.

[0159] The mass loss was calculated by comparing the mass of the dried sample after exposure to TRIS-buffered saline with the initial mass of the sample. The mass loss of PBF1 was: 42.0 ± 2.1% after 5 minutes, 47.3 ± 2.7% after 30 minutes, 51.5 ± 4.3% after 1 hour, 41.7 ± 5.7% after 3 hours, 70.1 ± 6.8% after 24 hours, and 100% after 48 hours.

[0160] The particle size of seven different PBF1 samples was measured using a Malvern Mastersizer 3000 laser diffraction particle size analyzer. The glass particles were suspended in distilled water to obtain an opacity value of 2-5%. Before analysis, the glass powder was stored in a vacuum desiccator and taken out for analysis, 3×5 analyses were performed, lasting about 20 seconds per analysis. The suspensions (n=5) were measured using blue (λ=470nm) and red (λ=632.8nm) lasers.

[0161] D×10(μm) D×50(μm) D×90(μm) PBF1.1 3.18 11.9 26.9 PBF1.2 3.44 10.5 22.2 PBF1.3 3.26 9.99 22.1 PBF1.4 N / A N / A N / A PBF1.5 3.35 12.3 27.4 PBF1.6 3.44 10.3 22.3 PBF1.7 4.84 13.2 27.1

[0162] Table 13. Particle size distribution of PBF1

[0163] Apatite formation in simulated body fluid was confirmed for PBF1, but not for CE1 or CE2. Simulated body fluid was synthesized according to the methods and instructions disclosed by Kokubo and Takadama (Kokubo, T. and Takadama, H., Biomaterials (2006) 27:15, pp. 2907-2915).

[0164] 1L batches of SBF were prepared in 1000mL Nalgene bottles (FEP bottles). Immediately after synthesis, the prepared SBF was stored at room temperature for 24 hours to ensure stability before experimental use. SBF was stored in Nalgene bottles with the caps tightly closed and kept at 6°C if not needed immediately (experimental use up to 30 days).

[0165] According to the TC04 method (published in Magon, ALB, Kim, TB, Valliant, EM et al., J Mater Sci: MaterMed (2015) 26: 115), 0.75 g of glass powder (n = 3) of each glass composition was immersed in 50 mL of SBF synthesized above in a polyethylene container. The container was then placed in an incubation orbital shaker at 37°C and stirred at 120 rpm for 3 time points: 30 minutes, 3 hours and 12 hours. After the time point, each sample was vacuum filtered with Whatman 42 or 5-grade filter paper (retaining particles of 2.5 μm) to collect solid material from the solution. The solid was immediately washed with distilled water and acetone to terminate any further reaction.

[0166] The filtered samples were dried in a vacuum desiccator for further analysis. Each sample was imaged using a Hitachi S-4700FEG (Hitachi, Chula Vista, Ca) scanning electron microscope at 1000x and 10000x magnification at 3KV and 15mA. The samples were mounted on a mount using double-sided carbon tape and sputtered with gold-palladium for 70 seconds (Leica EMACE200, Wetzlar, Germany). Scanning electron microscopy images of PBF1 at 30 minutes, 3 hours, and 12 hours are shown in Figure 11-14 middle.

[0167] Dentin tubule obstruction of PBF1 was also evaluated by developing an application protocol and statistical analysis of SEM images graded by two assessors according to a categorical obstruction scale. Human dentin sections (approximately 1-1.5 mm thick) were prepared from caries-free, unrestored molar crowns perpendicular to the long axis of the root using a diamond disk saw. Each section was etched with 10% citric acid for 2 minutes, then rinsed with water for 60 seconds, sonicated for 2 minutes, and rinsed with water for another 60 seconds. Each section was placed in a 25-mm diameter mold and covered with 3-mm-deep acrylic resin. Once the resin hardened, the dentin surface was polished to a mirror finish using 800 and 2500 grit sandpapers, respectively. After rinsing with deionized water, the surface was etched, sonicated, and rinsed again. The sample integrity, tubule density, and patency were examined again under optical microscopy and then with SEM.

[0168] A single dentin sample was assigned to each treatment group. Dentin samples were treated with (i) an unformulated mixture of exemplary glass particles; (ii) a test toothpaste including a mixture of exemplary glass particles or (iii) a control toothpaste without any other glass particles. The unformulated mixture was applied for 10 seconds using fingers wearing non-powdered nitrile gloves. The test and control toothpastes were applied to the samples for 10 seconds using an electric toothbrush. The toothpastes were left on for 30 seconds before rinsing until all visible toothpaste was removed. This operation was repeated for a total of 4 toothpaste applications.

[0169] Dentin samples were dried in an oven at 37 °C for 1 h, sputter-coated with gold, and observed using a Phenom ProX scanning electron microscope. Five images at 3000× magnification were taken from different parts of each sample, with the tubules perpendicular to the surface. Each 3000× micrograph was examined by two single-blind assessors for the degree of dentinal tubule obstruction according to a five-point classification scale. The grade classification was defined as:

[0170] 1. Occlusion (100% occlusion)

[0171] 2. Mostly occluded (75% occlusion)

[0172] 3. Equal (50% occlusion)

[0173] 4. Mostly unobstructed (25% occlusion)

[0174] 5. No occlusion (0% occlusion)

[0175] The mean score for each image was derived from the ratings of the two assessors. Although no formal statistical comparisons were performed because only one dentin sample was used for each treatment group, standard deviations were calculated.

[0176] Seven different treatment groups were tested, as shown in Table 14.

[0177]

[0178] Table 14. Treatment groups tested for dentinal tubule obstruction

[0179] As described above, each sample treatment group was tested on dentin samples and five SEM micrographs of each sample were taken at 3000 times. Each micrograph was evaluated by two assessors for classification. The average score of each micrograph and the five micrographs of each sample were combined to obtain the group average score and standard deviation (see Table 15).

[0180] Treatment Group Group mean (±SD) 1 4.90(±0.22) 2 1.50(±0.0) 3 2.90(±1.02) 4 2.40(±0.42) 5 3.60(±0.22) 6 3.60(±0.22) 7 3.20(±0.45)

[0181] Table 15. Average occlusion scores for different treatment groups

[0182] The mean baseline score for treatment group 1 was 4.90, indicating that virtually all dentinal tubules were unobstructed. The mean score for unformulated PBF1 rubbed directly into the dentin samples was 1.50, indicating almost complete tubular obstruction. Treatment groups 5, 6, and 7 (control groups lacking PBF1 or any other glass composition according to the present invention) had mean obstruction scores ranging from 3.2 to 3.6. The mean obstruction scores for treatment groups 3 and 4 (commercial toothpastes formulated with 5% or 15% PBF1 w / w) were lower, indicating a higher degree of tubular obstruction. When 15% w / w PBF1 was added, the commercial toothpaste Sensodyne TM The blocking level for Complete Protected increased from about 30% blocking (score 3.6) to about 50% blocking (score 2.5).

[0183] Dentin tubule obstruction by PBF1 was further evaluated using 5% w / w PBF1 sodium lauryl sulfate (SLS) paste. In this evaluation, PBF1-toothpaste and control toothpaste were applied to three different dentin samples for each treatment group. Each sample was brushed once with the treatment toothpaste for 2 minutes. Specifically, each dentin sample was brushed with 0.25 g of treatment toothpaste for 120 seconds and then rinsed with deionized water for 30 seconds. The average obstruction score for the 5% PBF1-SLS paste was 2.7±0.84. The average obstruction score for the SLS paste without PBF1 was 3.80±1.03. The results were obtained using Sensodyne TM The mean blocking score for the control test performed by Repair&Protect was 3.90±0.66.

[0184] PBF1-Na is prepared according to the scheme discussed above. Briefly, glass is synthesized in the following manner: 11.05g of B2O3, 3.36g of Na2CO3, 2.56g of MgO, 4.77g of CaCO3 and 1.33g of NaF (Sigma Aldrich, Canada) are weighed. The raw materials are mixed for 60 minutes to ensure uniformity. The blend is placed and filled in a 50mL platinum crucible (Zhengxin Matthey Group, Precious Metals Company, Pennsylvania). The filled crucible is then placed in a furnace (Jiabaolai, RHF 1600) at room temperature. The furnace is heated (25°C / min) to an initial holding temperature of 600°C and maintained for 60 minutes. The temperature is then raised (20°C / min) to a final holding temperature of 1200°C and maintained for 60 minutes. After pouring out, the glass melt is quenched between two stainless steel plates. The resulting quenched glass was ground / milled in a planetary micromill (Pulverisette 6, Fulsch, Germany) and sieved with a sieve conforming to ASTM E-11 (Cole Palmer, USA) to obtain particles smaller than 25 μm.

[0185] The particle sizes of ten different PBF 1-Na samples were measured as described above.

[0186] D×10(μm) D×50(μm) D×90(μm) PBF1-Na.1 4.7 14.9 35.2 PBF1-Na.2 4.6 14.4 31.2 PBF1-Na.3 4.2 13.3 29.9 PBF1-Na.4 4.5 14.1 30.7 PBF1-Na.5 4.3 12.0 26.7 PBF1-Na.6 4.4 13.9 30.5 PBF1-Na.7 4.1 12.1 26.2 PBF1-Na.8 4.3 12.2 25.5 PBF1-Na.9 4.0 11.8 25.7 PBF1-Na.10 4.2 13.3 29.7 average value 4.3 13.2 29.1

[0187] Table 16. Particle size distribution of PBF1-Na at 24 The density, % crystallinity and glass transition temperature of ten different samples were also measured as described above.

[0188]

[0189] Table 17 - Bulk Properties of PBF1-Na The mass loss and fluoride release after 24 hours of ten different samples were also measured as described above.

[0190] Glass Logo Mass loss (%) Fluoride release (ppm) PBF1-Na.1 70.3 92.0 PBF1-Na.2 71.7 91.2 PBF1-Na.3 71.7 88.9 PBF1-Na.4 73.3 88.4 PBF1-Na.5 73.0 87.5 PBF1-Na.6 73.3 95.0 PBF1-Na.7 72.0 98.8 PBF1-Na.8 72.0 93.9 PBF1-Na.9 72.7 94.2 PBF1-Na.10 73.3 97.6 average value 72.3 92.8

[0191] Table 18. Mass loss and fluoride release of PBF1-Na after 24 hours

[0192] In the foregoing description, for the purpose of explanation, many details are set forth in order to provide a thorough understanding of the examples. However, it will be apparent to those skilled in the art that these specific details are not required. Therefore, what has been described is merely an illustration of the application of the described examples, and many modifications and variations are possible in light of the above teachings.

[0193] Since the above description provides examples, it will be appreciated that those skilled in the art may make modifications and changes to the specific examples. Therefore, the scope of the claims should not be limited by the specific examples set forth herein, but should be interpreted in a manner consistent with the specification as a whole.

Claims

1. A glass composition comprising: about 50 mol % to about 95 mol % B2O3; about 5 mol % to about 50 mol % of one or more glass components selected from the group consisting of Li2O, Rb2O, K2O, Na2O, SrO, CaO, MgO and ZnO; 0 mol% CuO; Less than 0.1 mol% BaO; and Less than 0.1 mol% P2O5, in, The glass composition comprises less than 30 mol % of Rb2O, Wherein, the glass composition is at least a quaternary system, wherein the glass composition loses at least 5% by mass within 24 hours when exposed to a buffered saline solution, and The glass composition is a granular material comprising particles having a size of about 1 μm to about 50 μm.

2. A toothpaste comprising the glass composition according to claim 1.

3. A preventive paste comprising the glass composition according to claim 1.

4. A tooth varnish comprising the glass composition according to claim 1.

5. A dentin desensitizing composition comprising: (i) the glass composition according to claim 1; and (ii) An anhydrous orally compatible carrier.

6. A glass composition comprising: A fluoride providing about 5 mol % to about 10 mol % of CaF2, SnF2, NaF, KF, or any combination thereof, e.g., about 5 mol % CaF2 or about 10 mol % NaF; and about 90 mol % to about 95 mol % of a combination of B2O3, Na2O, MgO and CaO; in, Boron, magnesium, a combination of Na and any K, and a combination of Ca and any Sn in the glass composition are present in an element ratio of about 20: about 4: about 6: about 3, respectively. wherein the glass composition loses at least 5% by mass within 24 hours when exposed to a buffered saline solution, and Wherein, the glass composition is a granular material comprising particles having a size of about 1 to about 50 μm.

7. A toothpaste comprising the glass composition according to claim 6.

8. A preventive paste comprising the glass composition according to claim 6.

9. A tooth varnish comprising the glass composition according to claim 6.

10. A dentin desensitizing composition comprising: (i) the glass composition according to claim 6; and (ii) An anhydrous orally compatible carrier.

Citation Information

Patent Citations

  • Compositions containing bioactive glass and their use in treating tooth hypersensitivity

    US5735942A

  • Bioactive glass

    WO2007144662A1